Cost of Funds of Non-Bank Financial Institutions in Bangladesh: Internal Factors Analysis - Hossain, Md. Mosharref; Hossain, Md. Mahabbat (Asian Business Review, 2013)
Non-Bank Financial Institutions (NBFIs) are increasingly being recognized as complementary to the banking system and perform a diversified range of functions through offering various financial services to individual, corporate and institutional clients. Nevertheless, the cost of funds of NBFIs is significantly higher than the banks as banks are the prime sources of funds for them. On the other hand, the availability of funds from banks is becoming inadequate day by day due to the involvement of banks with some similar functions of NBFIs. The study intended to identify the current scenario of the cost of funds of different groups of NBFIs and to find out the causal relationship of the internal factors with the cost of funds of NBFIs. The study finds that NBFIs established before 1990 shows higher equity contribution and total asset size which shows their ability to generate funds at a low cost for the reputation and public confidence. On the other hand, due to the high equity contribution, large asset size and high EPS of the group of joint venture NBFIs compared to local NBFIs are able to raise relatively low cost funds. From the multiple regression analysis current study finds that only the variables of age and earning per share are statistically significant at 5% level. The other two factors, equity contribution and interest earning asset conform the theoretical sign although they are not statistically significant. The other variable, size of business that is measured by total asset, neither conform the expected sign nor is statistically significant.